2018
DOI: 10.1155/2018/3912326
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erythromycin and Tetracycline Resistance in Lactobacillus fermentum Strains

Abstract: Lactobacillus fermentum colonizing gastrointestinal and urogenital tracts of humans and animals is widely used in manufacturing of fermented products and as probiotics. These bacteria may function as vehicles of antibiotic resistance genes, which can be transferred to pathogenic bacteria. Therefore, monitoring and control of transmissible antibiotic resistance determinants in these microorganisms is necessary to approve their safety status. The aim of this study was to characterize erythromycin and tetracyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The safety standards of the European Food Safety Authority (EFSA) [82] and the generally recognized as safeGenerally Recognized as Safe (GRAS) designation of the US Food and Drug Administration (FDA) [83] demand stringent safety assessments of candidate probiotics [84]. In furtherance of this, virulence traits such as haemolysis and gelatinase were checked through functional assaying and found to be absent in NPL-99.…”
Section: Discussionmentioning
confidence: 99%
“…The safety standards of the European Food Safety Authority (EFSA) [82] and the generally recognized as safeGenerally Recognized as Safe (GRAS) designation of the US Food and Drug Administration (FDA) [83] demand stringent safety assessments of candidate probiotics [84]. In furtherance of this, virulence traits such as haemolysis and gelatinase were checked through functional assaying and found to be absent in NPL-99.…”
Section: Discussionmentioning
confidence: 99%
“…The most of isolates in this study showed an obvious resistance to chloramphenicol antibiotic. The target modifying may also contribute to chloramphenicol resistance, the efflux pump that is throwing away this antibiotic, causing decreasing of antibiotic concentration inside the bacterial cell (Anisimova and Yarullina 2018). The bacterial cell that has an ability to resisting the tetracycline antibiotic by many mechanisms such as hydrolyzing enzymes encoding by tet(X) genes, efflux pumps (A-E) types (Leski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For the genotyping, the genomic DNA of isolate was purified by using diaGene bacterial DNA extraction kit (Dia-M, Russia) from 10 ml of 24 h old culture grown under static anaerobic conditions. Then the gene of 16S rRNA was amplified by using universal 16S rRNA bacterial primers 27F (5′-GAG TTT GAT CCT GGC TCA G-3′) and 1392R (5′ ACG TT CC TG TA GA TT-3′) and Q5 DNA polymerase and sequenced (Evrogen JSC, Moscow) [15] , [16] , [17] , [18] . Species were identified on the basis of 16S rRNA gene sequences similarity obtained by its alignment with NCBI database using BLAST algorithm ( https://www.ncbi.nlm.nih.gov/BLAST ).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%